Levantamento das startups em construção civil no Brasil - Oliveira, Roberta Bastos de; Carvalho, Michele Tereza Marques (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
The lack of innovation in construction is often pointed out as the main factor for its unimpressivedevelopment. Some factors can be considered responsible as the difficulty of changing the mentality of theprofessionals and the implementation of new practices, besides the lack of investment and incentive.Startups make up the innovation ecosystem and then emerge as a way of filling some gaps found in theexperience. This article aims to show how is the national scenario regarding the development of startupsin construction, construtechs, in the last two years, as well as the existing incentive policies. Themethodology used was the online search for keywords besides a systematic exploration of the sources forfeeding the database and then a comparison of the results obtained with international publications fromWeb of Science regarding the impact and necessity of innovations in the construction. Some breaks weredetected in the bases consulted, evidencing the lack of communication between the academy and theexperience, and the non-propagation of the growth that the country apparently presented. As acontribution, this article was able to identify existing gaps and how startups can and should be exploredand disseminated for the progress of construction in Brazil.